Sifat elektrikal dan thermal nanokomposit HDPE/NPCC - Nurhajati, Dwi Wahini; Yuniari, Arum; Kasmudjiastuti, Emiliana (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2011)
abstrak